2017
DOI: 10.1371/journal.pone.0180224
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of calcifying cystic odontogenic tumors

Abstract: Calcifying cystic odontogenic tumors (CCOTs) are benign cystic tumors that form abnormally keratinized ghost cells. Mutations in CTNNB1, which encodes beta-catenin, have been implicated in the development of these tumors, but a causal relationship has not been definitively established. Thus, mutational hot spots in 50 cancer genes were examined by targeted next-generation sequencing in 11 samples of CCOT. Mutations in CTNNB1, but not in other genes, were observed in 10 of 11 cases. These mutations constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 26 publications
3
79
0
2
Order By: Relevance
“…In the present study, somatic gene mutation of POT was examined to discuss its possible pathogenesis. With respect to genetic alterations related to pathogenesis of benign odontogenic tumours or cysts, Braf V600E (Kurppa et al., ), Smo L412F and W535L (Sweeney et al., ) have been reported in ameloblastoma, while Ptch1 mutation has been reported in odontogenic keratocyst (Qu et al., ), Kras mutation in adenomatoid odontogenic tumours (Gomes et al., ), and Ctnnb1 mutations in calcifying odontogenic cysts (Sekine et al., ; Yukimori et al., ). Genetic alterations of Braf and Kras , Smo and Ctnnb1 affect to dysregulation of Mapk , Shh and Wnt signalling pathways, respectively, which play important roles in tooth germ development (Diniz et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, somatic gene mutation of POT was examined to discuss its possible pathogenesis. With respect to genetic alterations related to pathogenesis of benign odontogenic tumours or cysts, Braf V600E (Kurppa et al., ), Smo L412F and W535L (Sweeney et al., ) have been reported in ameloblastoma, while Ptch1 mutation has been reported in odontogenic keratocyst (Qu et al., ), Kras mutation in adenomatoid odontogenic tumours (Gomes et al., ), and Ctnnb1 mutations in calcifying odontogenic cysts (Sekine et al., ; Yukimori et al., ). Genetic alterations of Braf and Kras , Smo and Ctnnb1 affect to dysregulation of Mapk , Shh and Wnt signalling pathways, respectively, which play important roles in tooth germ development (Diniz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, somatic mutations of cancer‐associated genes such as Braf (Kurppa et al., ), Smo (Sweeney et al., ), Kras (Gomes et al., ), Ptch1 (Qu et al., ) and Ctnnb1 (Sekine et al., ; Yukimori et al., ) in some benign odontogenic tumours or cysts have been reported. These facts indicate that neoplastic proliferation of some odontogenic tumours may be triggered by genetic alterations affecting oncogenic signalling pathways (Diniz, Gomes, de Sousa, Xavier, & Gomez, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt/β‐catenin signaling pathway is involved in numerous processes in animal development, and its dysregulation is known to cause various abnormalities and tumors in humans . We previously reported that mutations in CTNNB1 , which encodes β‐catenin, are the major drivers of COCs, and are associated with the formation of ghost cells . However, the status of CTNNB1 mutations in DGCT and GCOC remains largely unknown…”
mentioning
confidence: 88%
“…Moreover, β‐catenin, which is encoded by CTNNB1 , was strongly detected in the nucleus by immunohistochemistry (Fig. b; immunohistochemistry was performed according to our previously reported procedures) …”
Section: Clinical Summarymentioning
confidence: 99%
“…The classification and terminology used to designate COC have evolved historically (Gorlin et al., ; Gold, ; Fejerskov & Krogh, ; Freedman, Lumerman, & Gee, ; Praetorius, Hjørting‐Hansen, Gorlin, & Vickers, ; Ellis & Shmookler, ; Colmenero, Patron, & Colmenero, ; Hirshberg, Kaplan, & Buchner, ; Shear, ; Toida, ). Therefore, inconsistencies in the terminology have occurred over time, reflecting the lack of precise knowledge about the pathogenesis, histology and behaviour of the lesions, as well as the overlapping definitions of tumours and cysts (Yukimori et al., ). In 2005 and until 2017, the WHO reclassified two odontogenic cysts (odontogenic keratocyst and COC) as neoplasms.…”
Section: Discussionmentioning
confidence: 99%